Detection of Oral Squamous Cell Carcinoma and Cervical Lymph Node Metastasis Using Activatable Near-Infrared Fluorescence Agents - Keereweer, Stijn; Mieog, J. Sven D; Mol, Isabel M; Van Driel, Pieter B. A. A; Snoeks, Thomas J. A; Baatenburg de Jong, Robert J; Vahrmeijer, Alexander L; Kerrebijn, Jeroen D. F; Löwik, Clemens W. G. M (Archives of otolaryngology--head & neck surgery, 2011)
OBJECTIVE To assess the feasibility of optical imaging using activatable near-infrared fluorescence (NIRF) agents to detect oral cancer and cervical lymph node metastasis in vivo. DESIGN In vivo study. SETTING University medical center. SUBJECTS Female nude mice aged 4 to 6 weeks. INTERVENTION Luciferase-expressing OSC-19-luc cells were injected into the tongues of nude mice. A control group of nude mice was injected in the tongue with a physiologic saline solution. Tumor growth was followed by bioluminescence imaging. After 3 weeks, animals were randomly allocated to intravenous administration of 1 of 2 activatable NIRF agents: ProSense680 or MMPSense680. Fluorescence imaging of the mice was performed, and the tumor to background ratio (TBR) was determined on histologic sections of the tongue and cervical lymph nodes after resection at necropsy. MAIN OUTCOME MEASURE Fluorescence signals. RESULTS The fluorescence signals in tongue tumor and cervical lymph node metastases were significantly higher than those in control animals. The mean (SD) TBR of ProSense680 in the tongue was 15.8 (8.1) and in the lymph nodes was 11.8 (3.6). For MMPSense680, the mean (SD) TBR in the tongue was 18.6 (9.4) and in the lymph nodes was 10.5 (4.0). CONCLUSIONS Oral cancer and cervical lymph node metastases can be detected by targeting increased proteolytic activity at the tumor borders using NIRF optical imaging. These NIRF agents could be used for real-time image-guided surgery, which has the potential to improve the complete surgical resection of oral cancer.Arch Otolaryngol Head Neck Surg. 2011;137(6):609-615-->